Differences between postmortem CT and autopsy in death investigation of cervical spine injuries - Makino, Yohsuke; Yokota, Hajime; Nakatani, Eiji; Yajima, Daisuke; Inokuchi, Go; Motomura, Ayumi; Chiba, Fumiko; Torimitsu, Suguru; Uno, Takashi; Iwase, Hirotaro (Forensic science international, 2017)
•Post-mortem CT and autopsy detect cervical spine injuries in different way.•Post-mortem CT more efficiently detects bone fractures than autopsy.•Autopsy more efficiently detects intervertebral injuries than post-mortem CT.•Accurate evaluation for cervical spine injuries requires the use of both methods. To clarify the differences between postmortem CT (PMCT) and autopsy findings in the postmortem detection of cervical spine injuries (CSIs). Our department’s forensic pathology database was searched for CSI cases. In each case, the autopsy data and radiologists’ interpretations were reviewed for the presence of bone fractures and intervertebral injuries. The study included 42 cases. For both bone fractures and intervertebral injuries, no substantial concordance between PMCT and autopsy findings was observed (McNemar’s test: p<0.001 and p<0.001, respectively). Regarding bone fractures, more injuries were detected with CT than with autopsy (CT: 74, autopsy: 23). The percentage of CT-detected fractures that were missed at autopsy (77.0%, 57/74) was higher than the percentage of autopsy-detected fractures missed with CT (26.1%, 6/23). Regarding intervertebral injuries, fewer injuries were detected with CT than with autopsy (CT: 40, autopsy: 80). The percentage of CT-detected injuries that were missed at autopsy (35.0%, 14/40) was lower than the percentage of autopsy-detected injuries that were missed with CT (67.5%, 54/80). A substantial number of CSIs were detected by either PMCT or autopsy alone. Accurate evaluation for CSI requires the use of both methods.